Implementasi Pembelajaran Berdiferensiasi dan Assesmen pada Kurikulum Merdeka di Sekolah Dasar Se-Kecamatan Sindang Kelingi, Kabupaten Rejang Lebong - Riwayanto Riwayanto (Institut Nalanda, 2024)
This research aims to find out about differentiated learning and assessment in the independent curriculum and how to implement it in elementary schools throughout Sindang Kelingi District. The aim of this research is formulated as follows; To find ou t how differentiated learning and assessment is implemented in the independent curriculum at the Sindang Kelingi District Elementary School? To find out what are the obstacles and advantages in implementing differentiated learning and assessment in the independent curriculum. This research uses a qualitative approach and the type of research is case study. The data was obtained by researchers by means of observation, interviews and documentation. Then the analysis method used is qualitative descriptive analysis, and data analysis techniques include data condensation, data presentation and drawing conclusions. Checking the validity of the data is carried out using diligent observation, triangulation, peer checking and using several reference materials. The research results show that the implementation of differentiated learning is carried out by mapping according to students' criteria, interests and needs.